A Historical Perspective of the Cultural and Religious Legacy of Raigarh - Verma, Aloke; Goswami, Payal (Integrated Journal for Research in Arts and Humanities, 2024)
Raigarh, a municipality in Chhattisgarh, India, is known for its scenic environment, abundant mineral deposits, and vibrant cultural legacy. Located near the Kelo River, Raigarh has evolved into a center for trade and cultural activities, shaped by the Raigarh Princely State and its kings, particularly Raja Chakradhar Singh. His support for Kathak dancing and his efforts in founding cultural institutions and organizing festivals have significantly impacted the region's identity. Established by the Gond dynasty in the 17th century, Raigarh experienced economic growth and social unity. Under the British Raj, Raigarh retained autonomy and improved infrastructure and administration. After independence, it transformed into a modern district, enhancing its importance. The annual Chakradhar Samaroh festival showcases the city's cultural liveliness. It is crucial to preserve Raigarh's cultural history amidst industrialization and globalization to maintain its distinct identity.